Private and Public Debt : Are Emerging Markets at Risk? - Bernardini, Marco (IMF Working Papers; Working Paper ;, 2017)
Using a dataset covering a large sample of emerging economies (EMEs), we study the relationship between debt and economic performance in bad times. While previous research has shown that private debt buildups exacerbate the duration and intensity of recessions in advanced economies (AEs), we document that this effect is very pronounced in EMEs as well. Moreover, although rapid public debt buildups are unlikely to be the primary trigger of financial crises, in EMEs they are associated with deeper and longer recessions than in AEs. Part of this difference is explained by a less supportive fiscal policy in EMEs during crises.